BRCA1 Promoter Methylation and Clinical Outcomes in Ovarian Cancer: An Individual Patient Data Meta-Analysis. (15th May 2020) - Kalachand, Roshni D; Stordal, Britta; Madden, Stephen; Chandler, Benjamin; Cunningham, Julie; Goode, Ellen L; Ruscito, Ilary; Braicu, Elena I; Sehouli, Jalid; Ignatov, Atanas; Yu, Herbert; Katsaros, Dionyssios; et al.
Abstract: Background: BRCA1 methylation has been associated with homologous recombination deficiency, a biomarker of platinum sensitivity. Studies evaluating BRCA1 -methylated tubal and ovarian cancer (OC) do not consistently support improved survival following platinum chemotherapy. We examine the characteristics of BRCA1 -methylated OC in a meta-analysis of individual participant data. Methods: Data of 2636 participants across 15 studies were analyzed. BRCA1 -methylated tumors were defined according to their original study. Associations between BRCA1 methylation and clinicopathological characteristics were evaluated. The effects of methylation on overall survival (OS) and progression-free survival (PFS) were examined using mixed-effects models. All statistical tests were 2-sided. Results: 430 (16.3%) tumors were BRCA1 -methylated. BRCA1 methylation was associated with younger age and advanced-stage, high-grade serous OC. There were no survival differences between BRCA1 -methylated and non– BRCA1 -methylated OC (median PFS = 20.0 vs 18.5 months, hazard ratio [HR] = 1.01, 95% CI = 0.87 to 1.16; P  =   .98; median OS = 46.6 vs 48.0 months, HR = 1.02, 95% CI = 0.87 to 1.18; P  =   .96). Where BRCA1/2 mutations were evaluated (n = 1248), BRCA1 methylation displayed no survival advantage over BRCA1/2 -intact ( BRCA1/2 wild-type non– BRCA1 -methylated) OC. Studies used different methods to define BRCA1 methylation. Where BRCA1 methylation was determined using methylation-specific polymerase chain reaction and gel electrophoresis (n = 834), it was associated with improved survival (PFS: HR = 0.80, 95% CI = 0.66 to 0.97; P  =   .02; OS: HR = 0.80, 95% CI = 0.63 to 1.00; P  =   .05) on mixed-effects modeling. Conclusion: BRCA1 -methylated OC displays similar clinicopathological features to BRCA1 -mutated OC but is not associated with survival. Heterogeneity within BRCA1 methylation assays influences associations. Refining these assays may better identify cases with silenced BRCA1 function and improved patient outcomes.